Activation of autophagy by elevated reactive oxygen species rather than released silver ions promotes cytotoxicity of polyvinylpyrrolidone-coated silver nanoparticles in hematopoietic cells. Issue 17 (12th April 2017) - Zhu, Lingying; Guo, Dawei; Sun, Lili; Huang, Zhihai; Zhang, Xiuyan; Ma, Wenjuan; Wu, Jie; Xiao, Lun; Zhao, Yun; Gu, Ning
Abstract : PVP-coated AgNPs induced autophagy via a ROS-mediated mTOR signaling pathway, which promoted the cytotoxic effect of these nanoparticles in Ba/F3 cells. Abstract : Silver nanoparticles (AgNPs) are the most commonly used engineered nanomaterials in commercialized products because of their antimicrobial activity. Previously, we have shown that polyvinylpyrrolidone (PVP)-coated AgNPs have an anti-leukemia effect against human myeloid leukemia cells; however, whether AgNPs are able to trigger autophagy in normal hematopoietic cells and the role of autophagy in AgNP-induced cytotoxicity remain unclear. In the current study, we observed that AgNPs were taken up by murine pro-B cells (Ba/F3), and then promoted accumulation of autophagosomes, which resulted from the induction of autophagy rather than the blockade of autophagic flux. AgNPs induced cytotoxicity in a dose-dependent manner accompanied by apoptosis and DNA damage through the production of reactive oxygen species (ROS) and the release of silver ions. The ROS-mediated mTOR signaling pathway was responsible for the induction of autophagy. More importantly, the inhibition of autophagy with the addition of 3-methyladenine (3-MA) or silencing of Atg5 significantly attenuated the cytotoxicity of AgNPs in Ba/F3. These findings suggest that autophagy is involved in the cytotoxicity of PVP-coated AgNPs in normal hematopoietic cells, and the inhibition of autophagy is a novel and potent strategy to protect normal hematopoietic cells upon treatment with AgNPs.